EPISTEMIC MODALITY: A CORPUS-BASED ANALYSIS OF EPISTEMIC MARKERS IN EU AND POLISH JUDGMENTS - KOŹBIAŁ, Dariusz (Comparative Legilinguistics, 2019)
The aim of this paper is to establish the repertoire and distribution of verbal and adverbial exponents of epistemic modality in English- and Polish-language judgments passed by the Court of Justice of the EU (CJEU) and non-translated judgments passed by the Supreme Court of Poland (SN). The study applies a model for categorizing exponents of epistemicity with regard to their (i) level (high-, medium- and low-level of certainty, necessity or possibility expressed by the markers; primary dimension), (ii) perspective (own vs. reported perspective), (iii) opinion (based either on facts or beliefs) and (iv) time (the embedding of epistemic markers in sentences relating to the past, present or future) (contextual dimensions). It examines the degree of intra-generic convergence of translated EU judgments and non-translated national judgments in terms of the employment of epistemic markers, as well as the degree of authoritativeness of judicial argumentation, and determines whether the frequent use of epistemic markers constitutes a generic feature of judgments. The research material consists of a parallel corpus of English- and Polish-language versions of 200 EU judgments and a corpus of 200 non-translated domestic judgments. The results point to the high salience and differing patterns of use of epistemic markers in both EU and national judgments. The frequent use of high-level epistemic markers boosts the authoritativeness of judicial reasoning.